Heart Failure and Hypothermia in an Infant: Pseudocyanide Syndrome? - J. Scott Baird (Case Reports in Critical Care)
Purpose. Mixed or central venous oxygen saturation has not been described during concurrent heart failure and hypothermia in children, both of which may be associated with hyperlactatemia. This report of an infant with heart failure and hypothermia is significant for increased inferior vena cava (IVC) oxygen saturation and hyperlactatemia. Case Report. A 36-day-old female was fussy for a day and then developed respiratory distress. In the Pediatric ER, she was tachycardic (260 beats/minute) and hypothermic (32.4 degrees C) with prolonged capillary refill and faint distal pulses. Adenosine was given twice via an intraosseous line for supraventricular tachycardia, with conversion to sinus rhythm. Blood drawn from an IVC catheter was significant for uncorrected (for temperature) oxygen saturation of 94% and lactate 18 mmol/L; corrected and uncorrected IVC oxygen saturation early during rewarming were >90%. During rewarming, declines in uncorrected IVC oxygen saturation and lactate correlated. Hypothermia and hyperlactatemia resolved after 10 and 12 hours. Conclusions. Concurrent heart failure and hypothermia in an infant were associated with increased IVC oxygen saturation and hyperlactatemia, similar to lab findings associated with a mitochondrial toxin such as cyanide. Improvement of heart failure and hypothermia were associated with resolution of these lab abnormalities, thus helping to rule out mitochondrial toxins. Additional reports may help better define a pseudocyanide syndrome in this setting.